2014
DOI: 10.1590/s1677-5538.ibju.2014.04.02
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of routine semen analysis and controversies surrounding the 2010 World Health Organization criteria for semen examination

Abstract: ARTICLE INFO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
115
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(120 citation statements)
references
References 55 publications
1
115
0
1
Order By: Relevance
“…This is due, in part, to the fact that conventional semen analysis does not assess the diverse array of biological properties that spermatozoa express as eminent specialized cells, or account for putative sperm dysfunctions that can be assessed by sperm DNA damage or seminal oxidative stress tests [Duran et al 2002;Esteves, 2014;Papillon-Smith et al 2015].…”
Section: Semen Analysismentioning
confidence: 99%
“…This is due, in part, to the fact that conventional semen analysis does not assess the diverse array of biological properties that spermatozoa express as eminent specialized cells, or account for putative sperm dysfunctions that can be assessed by sperm DNA damage or seminal oxidative stress tests [Duran et al 2002;Esteves, 2014;Papillon-Smith et al 2015].…”
Section: Semen Analysismentioning
confidence: 99%
“…We have also contemplated our own data involving 982 men seeking evaluation for infertility that had subnormal semen analysis results based on the 1999 WHO criteria. We found that approximately 39 % of these men would be reclassified as 'normal' by the new 2010 criteria [20]. The adoption of the most recent WHO reference values will likely result in more men classified as having a 'normal' semen analysis.…”
Section: Discussionmentioning
confidence: 84%
“…The aforementioned WHO reference values, however, differ substantially because reference values of the 2010 manual are markedly lower than those of the 1999 version. These differences pose a problem because the classification of patients with 'normal' and 'abnormal' semen analysis will depend on the version of the WHO manual [19,20]. In a recent study, up to 15 % of men with at least one parameter below the 1999 WHO reference values were reclassified as 'normal' because all parameters were at or above the 2010 WHO thresholds [21].…”
Section: Discussionmentioning
confidence: 99%
“…Нормативные показатели эякулята, предложенные в последнем издании Руководства Всемирной органи-зации здравоохранения (ВОЗ) по оценке и анализу эякулята (5-е издание (2010)) [2], вызвали полемику среди специалистов в области андрологии, спермато-логии и репродукции человека. Многие врачи-уроло-ги считают, что в связи с недостаточной строгостью предложенных критериев нарушения репродуктивной системы мужчин будут недооценены [3][4][5]. В послед-нем издании Руководства ВОЗ [2] использованы дан-ные из спермограмм мужчин, беременность у партнерш которых наступала в течение 12 мес половой жизни без предохранения.…”
Section: Introductionunclassified